Strategy improves profits through the right investment for households in Serikat Tolong Menolong Setia Sambu Baru Kecamatan Medan Barat - Fachrudin, Khaira Amalia; Siahaan, Elisabet; Ginting, Paham; Ginting, Liasta; Sipayung, Friska (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Investment is very important to be done in order to obtain benefits in the future. Housewives also need to make this investment. This service aims to provide investment strategies and open householder insights to be able to choose the right type of investment and assist her husband in deciding to invest or support investments made by her husband. Lectures and assistance were given to 25 housewives in STM Sambu Baru, Medan Barat District. After reading the profiles of these mothers it is recommended that the right investment is pure gold. The result is that mothers who have not had investment become interested in investing in gold. Previously they did arisan money, now they change their arisan, i.e. the arisan money is bought pure gold and will be given to the arisan draw. They also agreed to invite their husbands to invest in land and thought to have land investment in their own name.